2016
DOI: 10.18632/oncotarget.10864
|View full text |Cite
|
Sign up to set email alerts
|

Targeting hyperactivated DNA-PKcs by KU0060648 inhibits glioma progression and enhances temozolomide therapy via suppression of AKT signaling

Abstract: The overall survival remains undesirable in clinical glioma treatment. Inhibition of DNA-PKcs activity by its inhibitors suppresses tumor growth and enhances chemosensitivity of several tumors to chemotherapy. However, whether DNA-PKcs could be a potential target in glioma therapy remains unknown. In this study, we reported that the hyperactivated DNA-PKcs was profoundly correlated with glioma malignancy and observe a significant association between DNA-PKcs activation and survival of the glioma patients. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…5b), suggesting MCM3 knockdown reduced radioresistance. DNA-PKcs activation is critical for development of tumor therapy resistance [34, 35], cleaved PARP1 is a marker for apoptosis [36], we isolated tumors from mice, western blot assay showed that MCM3 knockdown inhibited the phosphorylation of DNA-PKcs, and increased PARP1 cleavage (Fig. 5c), suggesting MCM3 knockdown reduced radioresistance.…”
Section: Resultsmentioning
confidence: 99%
“…5b), suggesting MCM3 knockdown reduced radioresistance. DNA-PKcs activation is critical for development of tumor therapy resistance [34, 35], cleaved PARP1 is a marker for apoptosis [36], we isolated tumors from mice, western blot assay showed that MCM3 knockdown inhibited the phosphorylation of DNA-PKcs, and increased PARP1 cleavage (Fig. 5c), suggesting MCM3 knockdown reduced radioresistance.…”
Section: Resultsmentioning
confidence: 99%
“…Both Mo59K and U-87 MG have been shown to express high levels of activated DNA-PKcs (i.e. p-DNA-PKcs) in contrast to both normal human astrocyte cells and also the glioma cell lines A172 and H4 [17].…”
Section: Differences In Response Based Upon Cell Typementioning
confidence: 99%
“…Phospho-DNA-PK expression is significantly higher in human glioma than their respective adjacent non-tumorous tissue and correlates with malignant development and poor prognosis in glioma patients. 27 A recent transcriptome analysis identified DNA-PK as a predominant DNA repair enzyme in glioma stem cells (GSCs), which drives radiation resistance in GBM. 28 …”
Section: Dna-pk Inhibitorsmentioning
confidence: 99%